The Studies on the Armenian-Kypchak manuscripts in Turkey - Serikkazykyzy, Akbota; Avakova, Raushan (Turkic Studies Journal, 2023)
This article raises a question that has not been considered before. It refers to Turkish researchers’ studies of old Kypchak manuscripts, written in the Armenian alphabet in the 16th-17th centuries. During this period, due to historical events, Armenians and Kypchaks lived in the same settlement. Trade was especially active among Kypchaks and Armenians so kinship was established. This led to the formation of the Armenian-Kypchak language and writing. According to researchers, the Armenians who were living in Ukraine during the 16th-17th centuries forgot their native language and used the Kypchak as a spoken language and even they prayed in the Kypchak. In accordance with sources sources, only church ministers spoke Armenian. The Turkish-Armenian researcher K. Pamukchia, relying on the classification of Yak. Dashkevich, who studied the of Armenian-Kypchak written records, divides the development process of the Armenian-Kypchak language into three stages. The first is the mastery of the Kypchak language by the Armenians as a spoken language before the linguistic period (end of 13th -15th centuries). The second is the flourishing of the Armenian-Kypchak written language (start of 16th-first half of 17th century, i.e. 1524-1699). The third is the decline and death of the Armenian-Kypchak language (second half of 18th century).